If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(5 + m) + -6(m + 3) = 0 (5 * 9 + m * 9) + -6(m + 3) = 0 (45 + 9m) + -6(m + 3) = 0 Reorder the terms: 45 + 9m + -6(3 + m) = 0 45 + 9m + (3 * -6 + m * -6) = 0 45 + 9m + (-18 + -6m) = 0 Reorder the terms: 45 + -18 + 9m + -6m = 0 Combine like terms: 45 + -18 = 27 27 + 9m + -6m = 0 Combine like terms: 9m + -6m = 3m 27 + 3m = 0 Solving 27 + 3m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 3m = 0 + -27 Combine like terms: 27 + -27 = 0 0 + 3m = 0 + -27 3m = 0 + -27 Combine like terms: 0 + -27 = -27 3m = -27 Divide each side by '3'. m = -9 Simplifying m = -9
| s(8+2s+6)= | | 3*x=4*8 | | 11=3y+10 | | 3.5/5.2 | | 27.5/16.5 | | 9x^2y^6= | | k-39=18 | | 2.8/3.6 | | 7a-7=19+5a | | 3*x=5*10 | | 3/22= | | -2/3(6x-9)=-4x+6 | | 24=30-0.6m | | 96=3x+2x+6 | | x*x=2*16 | | 1/13= | | 3/7(49)= | | x*x=4*12 | | 2ln(4x-3)=4 | | 5/27= | | 2(x+3)-4x=5x+2 | | 5h+15-3h=2h | | 40+15n= | | 6*4=3*x | | 3/11= | | 5h+15=2h | | x*3=5*9 | | 2/11= | | 7x+6+x=1+4x-15 | | 3log(2x+4)=9 | | 24=30-2/3m | | 3b/5+5-8b/5=3 |